Neurodegenerative disorders associated with genes of mitochondria - Vaibhav S. Marde; Prerna L. Tiwari; Nitu L. Wankhede; Brijesh G. Taksande; Aman B. Upaganlawar; Milind J. Umekar; Mayur B. Kale (SpringerOpen, 2021)
Abstract Background Over the last decade, aggregating evidences suggested that there is a causative link between mutation in gene associated with mitochondrial dysfunction and development of several neurodegenerative disorders. Main text Recent structural and functional studies associated with mitochondrial genes have shown that mitochondrial abnormalities possibly lead to mitochondrial dysfunction. Several studies on animal models of neurodegenerative diseases and mitochondrial genes have provided compelling evidence that mitochondria is involved in the initiation as well as progression of diseases such as Parkinson's disease (PD), Alzheimer's disease (AD), Huntington's disease (HD), and Friedreich ataxia (FA). Conclusion In this mini-review, we have discussed the different etiologic and pathogenesis connected with the mitochondrial dysfunction and relevant neurodegenerative diseases that underlie the dominant part of mitochondrial genes in the disease development and its progress.